The Role of Islamic Religious Education in Students' Communication Ethics on Social Media - Rosy Dwi Arianti; Rosdialena (Journal Of Psychology, Counseling And Education, 2026)
The rapid development of information technology has made social media one of the most widely used communication platforms among students. However, the use of social media without adequate understanding of communication ethics can lead to various problems, such as the spread of hoaxes, hate speech, cyberbullying, and the use of inappropriate language. This study aims to analyze the role of Islamic Religious Education in shaping students' communication ethics on social media. The research employs a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation. The findings reveal that Islamic Religious Education plays a significant role in instilling values of honesty, responsibility, politeness, and mutual respect in digital communication. Through Islamic Religious Education, students gain a better understanding of the importance of maintaining ethical behavior while interacting on social media in accordance with Islamic teachings. Therefore, Islamic Religious Education serves as an important factor in fostering positive, responsible, and ethical communication behavior among students in the digital era.